PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN, DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PASIEN RAWAT INAP RSUD RAA SOEWONDO PATI - Errik Permana, 13.05.51.0102; Stiyawan, Mulyo Budi (Students Journal of Economic and Management, 2017)
This study examines the effect of the price perception of the hospital patient satisfaction tinap swamp RAA Soewondo Pati, the influence of service quality on patient satisfaction RAA Soewondo Hospital Pati, and the influence of corporate image on patient satisfaction RAA Soewondo Hospital Pati. This research was conducted in RSUD RAA Soewondo Pati. The number of samples in this study were100 respondents. The population in this study were all inpatients in hospitals RAA Soewondo Pati. The samples are determined by purposive sampling technique. Data is processed by using multiple regression aid from SPSS 19 program. The results showed price perceptions significant positive effect on patient satisfaction RAA Soewondo Hospital Pati, service quality significant positive effect on patient satisfaction RAA Soewondo Hospital Pati, corporate image significant positive effect on patient satisfaction RAA Soewondo Hospital Pati.Â Keywords: price perception, sevice quality, comporage image, satisfactionDaftar pustakaÂ A, Parasuraman. 2001. The Behaviorial Consequenses of Service Quality, Jurnal of Marketing. Vol 60.Adona, Fitri. 2006. Citra dan kekerasan dalam iklan. Perusahaan di Televisi. Padang Andalas University PressAaker,D.A. 1992.Strategic Market Management, John Wiley and Sons, New York Andreassen ,T. W. dan B. Lindestad. (1997). Customer Loyalty and Complex Services: The Impact of Corporate Image on Quality, Customer Satisfaction and Loyalty for Customers with Varying Degrees of Service Expertise. International Journal of Service Industry Management. 9(1): 7-23.Carpenter, J. M., and Fairhurst, A. 2005. Consumer Shopping Value, Satisfaction, And Loyalty For Retail Apparel Brands. Journal of Fashion Marketing andManagement, 9(3), 256â269.Fandy Tjiptono. (1999). Strategi Pemasaran. Yogyakarta: Cetakan ketiga,Andi.Fandy Tjiptono. (2000). Manajemen Jasa. Penerbit AndiYogyakarta.Fornell, C., et al. (1996). âThe American Customer Satiafaction Index: Nature, Purpose, and FIndingsâ. Journal of Marketing60, 7-18.Ghozali, Imam. (2011). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 19 (edisi kelima.) Semarang: Universitas Diponegoro.Hidayat, Rahmat. 2010. Pengaruh kualitas pelayanan, kualitas produk, dan nilai nasabah terhadap kepuasan dan loyalitas nasabah bank mandiri di jawa timur.Universitas truno Joyo Madura.Jarvenpaa, S.L., Todd, P.A., (1997). âConsumer reactions to electronic shopping on the world wide web. International Journal of Electronic Commerce 1 (2).59â88.kotler philip: amstrong .garry. 2008.). Prinsip prinsip pemasaran jilid 1 jakarta : erlangga)Kotler, Philip, 2009. Marketing Management, New Jersey, Prentice Hall Inc.Khan, Shahzad; Hussain, Syed Majid; Yaqoob, Fahad, 2012.Determinants of Customer Satisfaction in Fast Food Industry, International Journal of Management and Strategy, Vol. 3.Kotler, Philip. 2004. Marketing Insight from A to Z: 80 Konsep yang Harus Dipahami Oleh Setiap Manajer. Dialih bahasakan oleh: Anies Lastiati. Jakarta: Erlangga.Parasuraman,A, V, A. Zeithamldan L.L.Â Berry, !998, SERVQUAL: A multiple item scale for measuring customers perceptions of service quality, jurnal of retailing vol.64, no 1Purnama, Nursyaâbani. 2006. Manajemen Kualitas. Edisi Pertama. Yogjakarta : EKONISIAÂ Reynolds, K. E., and Beatty, S. E, 1999. Customer Benefits And Company Of Consequences Customer-Salesperson Relationships In Retailing. Journal ofRetailing, 75(1), 11â32.Sabri, Hasan, 2009. Pengaruh Kualitas Layanan, Citra, Nilai dan Kepuasan terhadap Loyalitas Pasien (Study Pada Industri Rumah Sakit Di Makasar), Fakultas Ekonomi Universitas Muslim IndonesiaSutanto, J. E. (2009). Dimension Quality of Service Influence Customer Satisfaction in the Hotel (A Case Study an Examination of the Transaction Model in Service Industry). Proceeding of International Seminar on Industrial Engineering and Management, Bali, Indonesia: 108-114.Soemirat, Ardianto. 2003. Dasar dasar Public Relation. Bandung PT. Remaja RosdakaryaÂ